EDUCATING CHILDREN TO BE A DISCIPLINE PERSON - Daviq Chairilsyah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The golden age is a critical period where parents must provide discipline as an initial foundation for children to be able to apply discipline early on. Cultivation of discipline needs to start as early as possible starting from within the family, the educational environment, and the community environment. This article will use the literature review method sourced from books and scientific journals in explaining the definition of discipline, the importance of discipline, and the discipline of learning strategies that can be carried out in early childhood. The purpose of writing this article is to give readers an understanding of the importance of discipline and strategies that can be done by parents and teachers in teaching discipline to young children.The things that can be done by parents and teachers is by practising the discipline of children routinely and consistently, getting used to behaving by values based on moral standards, and the need for parental control to develop internalized children. Besides, also recognize the age and stage of child development, invite children to talk from heart to heart, apply the consequences they receive when doing an action and finally give praise to the child when it is disciplined